Improved Thermal Stability and Wettability Behavior of Thermoplastic Polyurethane/Barium Metaborate Composites - (:unkn) unknown (UNIV FED SAO CARLOS, DEPT ENGENHARIA MATERIALS, 2016)
In this paper, it was targeted to the enhance thermal stability and wettability behavior of thermoplastic polyurethane (TPU) by adding barium metaborate. TPU-Barium metaborate composites were prepared by adding various proportions of barium metaborate to TPU. The chemical structures of the composites were characterised by fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) analysis. All prepared composites have extremely high Tg and thermal stability as determined from DSC and TGA analysis. All composite materials have the Tg ranging from 15 to 35 degrees C. The surface morphologies of the composites were investigated by a scanning electron microscopy. Mechanical properties of the samples were characterized with stress-strain test. Hydrophobicity of the samples was determined by the contact angle measurements. The obtained results proved that thermal, hydrophobic and mechanical properties were improved.
Keywords: Barium metaborate; thermoplastic polyurethane (TPU); polymer composite; surface properties; MECHANICAL-PROPERTIES; CARBON NANOTUBES; NANOCOMPOSITES; DEFORMATION; MORPHOLOGY; FOAMS